Panel Data Regression Modelling on The Analysis of The Influence Of Fiscal Decentralization to Poverty In Maluku In 2020-2024 - Bachtiar, Bayu Aji; Sa'adah, Miftahus (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
Maluku Province persistently records one of the highest poverty rates in Indonesia, despite sustained fiscal transfers from the central government. This study examines the relationship between fiscal decentralization and poverty reduction in Maluku from 2020 to 2024 through a panel data regression approach, enabling simultaneous analysis of spatial and temporal variations across districts. Poverty data were sourced from Badan Pusat Statistik (BPS) and fiscal variables from Direktorat Jenderal Perimbangan Keuangan (DJPK). The empirical results demonstrate that Regional Original Revenue (PAD), general allocation funds (DAU), and village funds (DD) exert statistically significant negative effects on poverty rates, with DD showing the strongest marginal impact. By focusing on a structurally disadvantaged province, this study contributes to the empirical literature by providing region-specific evidence on the effectiveness of fiscal decentralization mechanisms in reducing poverty. The findings underscore the importance of strengthening local fiscal capacity and optimizing the allocation of intergovernmental transfers to achieve more equitable and sustainable poverty alleviation.